Efforts to strengthen pancasila as a state ideology through an educational approach - Sasmita, Saepudin Karta; Handayani, Dini; Hariyanti, Hariyanti (Universitas Tanjungpura, 2025)
This paper aims to describe the historicity of the birth of the conception of Pancasila as well as the pros and cons that arise regarding the creators of Pancasila and efforts to internalize Pancasila in the educational approach in schools through extracurricular activities. This article uses the literature review method in analyzing problems and finding solutions through theoretical analysis and research results on related problems. Based on document analysis, it is known that Pancasila is the work of the Indonesian nation which is extracted from noble cultural values, Soekarno only dug up these pearls and formulated them in one conception called Pancasila, but this conception is different from the Pancasila currently in effect as approved by PPKI on 18 August 1945 as state ideology. Pancasila must continue to be internalized, especially in the educational approach, not only through subjects in class but also through ideological intelligence extracurricular activities. An idea to return to making Pancasila easy to discuss but in an educative way, not indoctrinative.